Contrast-Enhanced Ultrasound in Residual Tumor of Hepatocellular Carcinoma following Transarterial Chemoembolization: Is It Helpful for Tumor Response?. (2nd August 2018) - Jiang, Tian'an; Zhao, Qiyu; Huang, Min; Sun, Junhui; Tian, Guo
Abstract : Aim . To investigate the enhancement pattern of residual tumor on contrast-enhanced ultrasonography (CEUS) in patients with hepatocellular carcinoma (HCC) treated with transarterial chemoembolization (TACE). Methods . Our study initially included 76 patients with HCC, 73 of which were finally allocated into two groups: group 1 (43 patients, post-TACE group) and group 2 (30 patients, untreated HCC group). All patients were performed with CEUS using SonoVue, and qualitative and quantitative enhancement characteristics (rise time, peak time, and washout time) were evaluated for the residual tumors. T test orχ 2 test was used to estimate for differences between two groups. Results . In group 1, the mean rise time, peak time, and washout times in group 1 were 16.1±2.7 sec, 31.3±3.1 sec, and 191.0±31.3 sec, respectively. In group 2, these were 15.1±3.5 sec, 30.9±3.2 sec, and 142.6±16.1 sec, respectively. The differences in rise time and peak time were not statistically significant ( P =0.09 and 0.30, respectively), but the washout time was significantly prolonged in group 1 ( P <0.01). The enhanced pattern in arterial phase was inhomogeneous (n=11), regular homogeneous (n=11), partial (n=12), peripheral (n=7), and peripheral rim-like (n=2) in group 1. The average of the longest tumor size of the whole lesion in the 5 types was 4.7±1.3cm, 2.9±1.0cm, 3.1±1.7cm, 2.5±0.6cm, and 2.1 cm. Conclusion . It suggested that the washout time of post-TACE residual lesions was prolonged compared with untreated HCC nodules on CEUS imaging. Combined with the triple-phase enhancement pattern seen on CEUS, the washout time may provide additional information to guide further treatment for residual tumors.